Performance comparison of differential evolution and particle swarm optimization in constrained optimization - Iwan, Mahmud; Akmeliawati, Rini; Faisal, Tarig; Al-Assadi, Hayder M.A.A. (Elsevier, 2012)
Optimization appears in many aspects of engineering problems. There are quite numbers of modern optimization algorithms proposed in the last two decades to solve optimization problems. Particle swarm optimization (PSO) and differential evolution (DE) are among the well-known modern optimization algorithms. This paper presents a comparative study for min-max constrained optimization using PSO and DE. Here, the constrained optimization is represented by some selected standard benchmark functions. A new constraint handling and stopping criterion technique is also adopted in the optimization algorithm. Generally, in terms of repeatability and the quality of the obtained solutions, DE outperforms PSO.